2016
DOI: 10.1007/s40095-016-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

The development of fly ash-supported CaO derived from mollusk shell of Anadara granosa and Paphia undulata as heterogeneous CaO catalyst in biodiesel synthesis

Abstract: The aim of this study was to develop fly ash-supported CaO catalyst derived from waste mollusk shell of Anadara granosa and Paphia undulata for transesterification of palm oil to yield biodiesel. The active precursor Ca(OH) 2 of the catalyst has been developed from calcination of waste mollusk shell, while the mesoporous has been prepared using the wet impregnation method. The results demonstrated that the mollusk shell-derived catalyst could gain the yield of biodiesel of 92 and 94 % for A. granosa shell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Between these shells, the catalytic performance of apple snail shell was found to be better in biodiesel conversion because of its higher surface area compared to meretrix venus shell. Among different mollusk species, Pila globosa (Agrawal et al, 2012), Anadara granosa (Hadiyanto et al, 2016a;Hadiyanto et al, 2016b), Paphia undulate (Hadiyanto et al, 2016a), and Margaritifera falcate (Madhuvilakku et al, 2013) were commonly used species by researchers for the extraction of calcium oxide. It has also been reported that the desired calcination temperature ranges from 800 °C to 900 °C to draw better catalytic activity from mollusk shells.…”
Section: Mollusk Shellsmentioning
confidence: 99%
“…Between these shells, the catalytic performance of apple snail shell was found to be better in biodiesel conversion because of its higher surface area compared to meretrix venus shell. Among different mollusk species, Pila globosa (Agrawal et al, 2012), Anadara granosa (Hadiyanto et al, 2016a;Hadiyanto et al, 2016b), Paphia undulate (Hadiyanto et al, 2016a), and Margaritifera falcate (Madhuvilakku et al, 2013) were commonly used species by researchers for the extraction of calcium oxide. It has also been reported that the desired calcination temperature ranges from 800 °C to 900 °C to draw better catalytic activity from mollusk shells.…”
Section: Mollusk Shellsmentioning
confidence: 99%
“…The sediment of fly ash was collected and dried at room temperature for 1 day to reduce the moisture content. Limestone powder and fly ash were mixed with a weight ratio of 1:1 through wet and dry methods [20]. The dry method was conducted by directly mixing the powdered limestone and fly ash.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…In industries, the activated P. undulata shells waste can be utilized as a cost-effective catalyst for biodiesel synthesis from nonvegetable oil, and the y ash-supported CaO catalyst derived from the waste shell of P. undulata is used for transesteri cation of palm oil to yield biodiesel (Nurdin et al 2014;Hadiyanto 2016). Bioceramic derived from P. undulata waste shell is used as alternative bone material for the vertebral bones that consist of cervical, lumbar and spongy bones (Mohammad et al 2012).…”
Section: Introductionmentioning
confidence: 99%